"Being Stuck between Two Worlds" – Identity Configurations of Occupational and Family Identities. Issue 4 (2nd October 2019) - Gyberg, Fanny; Frisén, Ann; Syed, Moin
ABSTRACT: Most research on identity has focused on either identity processes or identity content, neglecting how individuals structure their identities. We investigated how individuals negotiated their sometimes conflicting multiple identifications of work and family into different types of workable identity configurations. We also examined differences across configurations in the gender distribution, degree of conflict, and life satisfaction. Through a mixed methods approach, a community sample of 124 young Swedish adults (50% women, M age 33.29 years) were interviewed about work and family priorities and completed a rating scale measure of life satisfaction. The qualitative analyses showed six different types of identity configurations, the most common being Family first, followed by Everything is important, Struggling to prioritize, Now family comes first, Inability to prioritize, and Work first . The quantitative analyses showed few gender differences across configurations, but there were differences in conflict and life satisfaction between configurations. The findings from this study reflect the complex and dynamic ways identity is structured within a cultural context.